Circadian clock-related genetic risk scores and risk of placental abruption. Issue 12 (December 2015) - Qiu, Chunfang; Gelaye, Bizu; Denis, Marie; Tadesse, Mahlet G.; Luque Fernandez, Miguel Angel; Enquobahrie, Daniel A.; Ananth, Cande V.; Sanchez, Sixto E.; Williams, Michelle A.
Abstract: Introduction: The circadian clock plays an important role in several aspects of female reproductive biology. Evidence linking circadian clock-related genes to pregnancy outcomes has been inconsistent. We sought to examine whether variations in single nucleotide polymorphisms (SNPs) of circadian clock genes are associated with PA risk. Methods: Maternal blood samples were collected from 470 PA case and 473 controls. Genotyping was performed using the Illumina Cardio-MetaboChip platform. We examined 119 SNPs in 13 candidate genes known to control circadian rhythms (e.g., CRY2, ARNTL, and RORA ). Univariate and penalized logistic regression models were fit to estimate odds ratios (ORs); and the combined effect of multiple SNPs on PA risk was estimated using a weighted genetic risk score (wGRS). Results: A common SNP in the RORA gene (rs2899663) was associated with a 21% reduced odds of PA (P < 0.05). The odds of PA increased with increasing wGRS (Ptrend  < 0.001). The corresponding ORs were 1.00, 1.83, 2.81 and 5.13 across wGRS quartiles. Participants in the highest wGRS quartile had a 5.13-fold (95% confidence interval: 3.21–8.21) higher odds of PA compared to those in the lowest quartile. Although the test for interaction was not significant, the odds of PA was substantially elevated for preeclamptics with the highest wGRS quartile (OR = 14.44, 95%CI: 6.62–31.53) compared to normotensive women in the lowest wGRS quartile. Discussion: Genetic variants in circadian rhythm genes may be associated with PA risk. Larger studies are needed to corroborate these findings and to further elucidate the pathogenesis of this important obstetrical complication. Highlights: Genetic variations in circadian clock genes are associated with risk of placental abruption (PA). The weighted genetic risk score (wGRS) did not appear to influence the timing of PA. There was some suggestive evidence of an effect modification between wGRS and preeclampsia on PA.